Pseudomonas glycinae sp. nov. isolated from the soybean rhizosphere - Jia, Jiayuan (Microbiologyopen, 2020)
Strains MS586(T) and MS82, which are aerobic, Gram‐negative, rod‐shaped, and polar‐flagellated bacteria, were isolated from the soybean rhizosphere in Mississippi. Taxonomic positions of MS586(T) and MS82 were determined using a polyphasic approach. 16S rRNA gene sequence analyses of the two strains showed high pairwise sequence similarities (>98%) to some Pseudomonas species. Analysis of the concatenated 16S rRNA, rpoB, rpoD, and gyrB gene sequences indicated that the strains belonging to the Pseudomonas koreensis subgroup (SG) shared the highest similarity with Pseudomonas kribbensis strain 46‐2(T). Analyses of average nucleotide identity (ANI), genome‐to‐genome distance, delineated MS586(T) and MS82 from other species within the genus Pseudomonas. The predominant quinone system of the strain was ubiquinone 9 (Q‐9), and the DNA G+C content was 60.48 mol%. The major fatty acids were C(16:0), C(17:0) cyclo, and the summed features 3 and 8 consisting of C(16:1)ω7c/C(16:1)ω6c and C(18:1)ω7c/C(18:1)ω6c, respectively. The major polar lipids were phosphatidylglycerol, phosphatidylethanolamine, and diphosphatidylglycerol. Based on these data, it is proposed that strains MS586(T) and MS82 represent a novel species within the genus Pseudomonas. The proposed name for the new species is Pseudomonas glycinae, and the type strain is MS586(T) (accession NRRL B‐65441 = accession LMG 30275).